2016
DOI: 10.2147/ijn.s98547
|View full text |Cite
|
Sign up to set email alerts
|

Rationally designed nanocarriers for intranasal therapy of allergic rhinitis: influence of carrier type on in vivo nasal deposition

Abstract: The aim of this study is to develop a locally acting nasal delivery system of triamcinolone acetonide (TA) for the maintenance therapy of allergic rhinitis. The effect of encapsulating TA in different nanocarriers on its mucosal permeation and retention as well as in vivo nasal deposition has been studied. A comparative study was established between polymeric oil core nanocapsules (NCs), lipid nanocarriers such as nanoemulsion (NE), and nanostructured lipid carriers (NLCs). The elaborated nanocarriers were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The results showed that NCs with sizes in the range of 200-570 nm led to hypocalcemic effects that were considerably enhanced and prolonged compared to the corresponding salmon calcitonin nanoemulsion or to the aqueous solutions with chitosan. Sallam et al [162] developed a locally acting nasal delivery system of triamcinolone acetonide using different nanosystems. The NCs composed of a Capryol ® oily core and Eudragit RS100 provided the highest mucosal retention compared to the NEs and NLCs with the least permeation, thus the drug was retained on the nasal mucosa.…”
Section: Nanocapsules (Ncs)mentioning
confidence: 99%
“…The results showed that NCs with sizes in the range of 200-570 nm led to hypocalcemic effects that were considerably enhanced and prolonged compared to the corresponding salmon calcitonin nanoemulsion or to the aqueous solutions with chitosan. Sallam et al [162] developed a locally acting nasal delivery system of triamcinolone acetonide using different nanosystems. The NCs composed of a Capryol ® oily core and Eudragit RS100 provided the highest mucosal retention compared to the NEs and NLCs with the least permeation, thus the drug was retained on the nasal mucosa.…”
Section: Nanocapsules (Ncs)mentioning
confidence: 99%
“…A prerequisite for successful topical vaginal therapy is the formulation’s ability to guarantee a prolonged contact with the vaginal mucosa [ 38 ]. For this reason, mucoadhesive properties were investigated by measuring the turbidity at 650 nm of vesicle suspensions in the presence of mucin [ 16 , 39 , 40 ]. An increased turbidity with respect to the control (vesicle suspension without mucin) implies a greater mucoadhesion.…”
Section: Resultsmentioning
confidence: 99%
“…Mucoadhesive properties were investigated by measuring the turbidity of the suspensions containing phospholipid vesicles together with mucin [ 16 , 39 , 40 , 55 ]. Mucin was dispersed in water (0.08% w/v ) for 6 h. Subsequently, the mucin dispersion was centrifuged at 7500 rpm (GS-15R Centrifuge, Beckman Coulter, Milan, Italy) for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…To remove the limitation of applying miRNA in the nasal mucosa, we sought to design a safe and stable formulation to deliver miR-146afor the local treatment of allergic rhinitis. According to the unique pH (5.5–7.8) and temperature (32–35 °C) of the nasal cavity [ 21 , 22 , 23 ], a thermosensitive in situ hydrogel was designed that is liquid at room temperature for easy preparation and administration with a controllable dosage ( Scheme 1 ). After reaching the lesion area, it should be transformed into gel to increase retention time.…”
Section: Introductionmentioning
confidence: 99%